Not real problems, but unknown electronic devices - Julio Carabaña Morales (ADIDE Federación, 2014)
According to PISA 2012, Spanish students did score still worse in Problem Solving than in Reading, Mathematics and Science, a result that has produced a certain alarm and a lot of diagnoses and remedies. In this paper, I first use OCDE's data and analyses to show that the main cause of this difference among Problem Solving and Reading, Mathematics and Science has been the Computer Based Administration of the Problem Solving test.  Second, I suggest some  hypotheses about why the OCDE ignores its own finding about the lack of validity of this test.